Physiological, anthropometric and podiatrists characteristics in a professional basketball team - Ramos, D.; Mendizabal, S.; Moreno, R.; Rubio, J. A.; Martin, F.; Jiménez, F. (Archivos de medicina del deporte, 2008)
The study of physiological, psychological and functional characteristics of players from different sports has been a point of interest. In basketball is no less need and there are approximations in the sport in physical and psychological terms. These decalogue has provided information on high performance athletes and has helped us detected new sport talents and to facilitate the training process at all stages. Materials and methods: Subjects: Twelve professional ACB league basketball players took part in this study (age= 26.66 ± 5.88 years); (height = 199.59 ± 9.79cm); (weight = 98.33 ± 14.84kg). Instruments: the anthropometrics characteristics were obtained using Seca height and a body composition analyzer by bioelectrical impedance (Inbody720). The test was conducted in a VO2max HP Cosmos Saturn treadmill with the gas analyzer CPX Ultima and Footwork Pro pressures platform was used in a plantar test. Protocol: the data capture was made by measuring the height in the fi rst place, then was analyzed the body composition, was continued the bipodal static test of support at key positions. To fi nish was made VO2max test on the treadmill until exhaustion with progressive increase in slope and speed of stadiums of a minute. Variables: The following were obtained anthropometric measurements: height, weight, skeletal muscle mass (MME) body fat (% and Kg), body balance, intracellular water, extracellular water, proteins and minerals. Study of plantar pressure was obtained: medium and maximum pressure planting of each foot, equidistant to the centre of pressure on both feet, and mass distribution between each foot and the treadmill test was acquired VO2max and maximum heart rate. Results: Anthropometrics results has showed that our basketball players have a weight of 98.33±14.84 Kg, 49.4±8.38 Kg of which are muscle skeletal mass. The fat mass percentage has been 13.81%±4.24. The Table 1 shows the different body composition variables. Physiologically, subjects has had 50.4±4.11 ml/Kg/min from VO2max and 179±9 bpm from maximum heart rate. The plantar pressure study has showed a mean of 0.39-0.35±0.07-0.07 Kgf/cm2, a maximum pressure of 1.44-1.43±0.35-0.45 Kgf/cm2 and a weight distribution between the two feet of 51.08±5.12 and 48.92±5.12 %. Conclusions: Across the morphologic, physiological information and the plantar analysis has defi ned the profi le of professional basketball players. The acquisition of descriptive data for each subject in the evaluation of functional characteristics of lower limb had provided us with values that we normally serve as a reference to recovery of possible injuries produced during the season.